Gene Copy Number Quantification of SHOX , VAMP7 , and SRY for the Detection of Sex Chromosome Aneuploidies in Neonates - Ibarra Ramírez, Marisol; Lugo Trampe, José de Jesús; Campos Acevedo, Luis Daniel; Zamudio Osuna, Michelle de Jesús; Torres Muñoz, Iris Carmen; Gómez Puente, Viviana; García Castañeda, Gloria; Arredondo Vásquez, Patricia del Carmen; Rodríguez Sánchez, Irám Pablo; Schaeffer, Satu Elisa; Velasco Sepúlveda, Braulio Hernán; Villarreal Pérez, Jesús Zacarías; et al. (Mary Ann Liebert, 2020)
Aims: To explore the feasibility of detecting sex chromosome aneuploidies (SCAs) by means of gene copy number quantification of short stature homeobox (SHOX), vesicle-associated membrane protein 7 (VAMP7), and SRY in newborns. Materials and Methods: Gene doses of SHOX, VAMP7, and SRY were determined by quantitative polymerase chain reaction (qPCR) using DNA obtained from dried blood samples from newborns. Relative quantification values were obtained. An aneuploidy profile was established according to cutoff values. Samples with ≥2 gene doses (out of range) were reanalyzed, and those with aneuploidy profiles were confirmed by karyotyping. Sensitivity, specificity, and positive and negative predictive values were obtained. Results: A total of 10,033 samples were collected (4945 females and 5088 males). Of 244 (2.43%) samples with ≥2 gene doses that were retested, 20 cases were confirmed. The overall incidence of SCAs was 1 in 500 live newborns. There were six cases of Turner syndrome (1/824), 3 cases of XXX (1/1648), 7 cases of Klinefelter syndrome (1/726), and 4 cases of of XYY (1/1272). The sensitivity was 0.952 (95.24%), specificity of 0.975 (97.56%), positive predictive value of 0.909 (90.91%), and negative predictive value of 0.987 (98.77%). Conclusions: Gene copy number analyses of VAMP7, SHOX, and SRY genes by qPCR from blood samples spotted onto filter paper is a highly reliable method for the early detection of male and female SCAs.